The Simultaneous Effect of Aerobic Exercise and Matricaria chamomilla L. Flower Extract on the Serum Level of Peptide C in Streptozotocin-Induced Diabetic Rats - Naser Mirazi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2019)
Background and Objectives: Serum level of C peptide is considered as one of the indicators of diabetes treatment process. In this study, simultaneous effect of aerobic exercise and Matricaria chamomilla L. flower (MFE) extract, was investigated on the serum level of C peptide in male diabetic rats.